Luta de classes e o programa nacional de educação na reforma agrária: a disputa ideológica da educação no Maranhão - MACEDO, Marinalva Sousa (2022)
The work has as its object of study the classs truggle and the National Education Program - PRONERA, highlighting the tensions and contradictions around its creation and its development path, considering that its creation took place between the latifundium crisis and the emergence of agribusiness reshaping the class struggle in the countryside, whose historic landmark was the holding of the I National Meeting of Educators of Agrarian Reform - I ENERA, reaffirmed in the I and II National Conferences for Basic Rural Education, which aimed to strengthen the struggle for quality public education for rural people. Since then, social and trade union movements, throughout their existence, have been fighting for Agrarian Reform and for public policies for the peasant population, they have been able to advance, on different fronts, achievements in the context of the formulation of milestones. regulatory and legal instruments, including transforming the Program into a public policy, with a view to ensuring Rural Education. In the particularity of analysis, the class struggle and PRONERA in the countryside in Maranhão were taken as an object of study, adopting as an empirical reference the experience in the field of education of the Movimento dos Trabalhadores Rurais Sem Terra – MST, in Settlement Areas in Maranhão – ASSEMA and the Federation of Agricultural Workers and Agriculturists of the State of Maranhão - FETAEMA, the most expressive movements in the field of Rural Education and the first applicants for courses by PRONERA for their Agrarian Reform settlement areas and also for qualification of its operating bases. Thus, in order to find out how PRONERA makes up the class struggle in the countryside of Maranhão, interviews were carried out with peasant and union leaders and graduates of PRONERA courses demanded by these Movements. The research shows that PRONERA has brought important contributions to Rural Education, to the production and qualification of the base of these movements, in particular, the MST and ASSEMA, helping to strengthen the organization and resistance of peasants in Maranhão. For this understanding, the categories of Class Struggle, State, Rural Education, PRONERA were used.